Age and educational track influence adolescent discounting of delayed rewards - Lee, Nikki C.; De Groot, Renate H.; Boschloo, Annemarie; Dekker, Sanne; Krabbendam, Lydia; Jolles, Jelle (Frontiers in Psychology, 2013)
This study examined age-related changes in a specific aspect of adolescent decision-making, namely the preference for future versus immediate outcomes. A sample of 622 Dutch adolescents aged 12 -17 years completed a temporal discounting task. Participants were asked to choose between a delayed reward of €50 or an immediate reward of lower value. The delay interval was varied in three blocks (1 week, 1 month, 6 months). Results showed that preferences for large delayed rewards over smaller immediate rewards increased with age: late adolescents made more long-term decisions than early adolescents. This change was related to educational track. In the lower educational track, an age-related decrease in discounting was found for all three delay intervals. In the higher educational track this decrease only occurred for the six month delay interval. However, across all delay intervals enrolment in a higher level educational track was associated with an increased preference for long-term rewards. These results suggest that late adolescents are less susceptible to the competing presence of an immediate reward when making long-term decisions, a skill which becomes increasingly important as they transition into adulthood.